2004
DOI: 10.1124/dmd.32.7.685
|View full text |Cite
|
Sign up to set email alerts
|

C-Jun N-Terminal Kinase Modulates 1,25-Dihydroxyvitamin D3-Induced Cytochrome P450 3a4 Gene Expression

Abstract: Cytochrome P450 (P450) plays an important role in the oxidative metabolism of numerous endogenous and exogenous compounds. In humans, cytochrome P450 3A4 (CYP3A4) is the predominant P450 isoform in the liver and small intestinal epithelial cells (Watkins et al., 1987;Paine et al., 1997) and is responsible for the metabolism of more than 60% of therapeutic drugs. Intestinal CYP3A4 is thought to contribute to the first-pass metabolism of orally administered drugs . The CYP3A4 gene is inducible by many xenobiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…VD 3 was reported to induce CYP3A4 expression through the c-Jun NH 2 -terminal kinase pathway in Caco-2 cells (Yasunami et al, 2004). Therefore, LCA may be able to stimulate the c-Jun NH 2 -terminal kinase pathway as in the case of VD 3 .…”
Section: Discussionmentioning
confidence: 99%
“…VD 3 was reported to induce CYP3A4 expression through the c-Jun NH 2 -terminal kinase pathway in Caco-2 cells (Yasunami et al, 2004). Therefore, LCA may be able to stimulate the c-Jun NH 2 -terminal kinase pathway as in the case of VD 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature about the interaction between JNK and vitamin D do not support this concept. Yasunami et al (2004) demonstrated that SP600125 dose-dependently inhibited the CYP3A4 promoter activity induced by 1,25(OH) 2 D 3 ; however, SP600125 did not affect 1,25(OH) 2 D 3 -induced transactivation of the DR3 via VDR. Buitrago et al (2011) showed that 1,25(OH) 2 D 3 promotes the phosphorylation of JNK 1/2, the response was fast and maximal phosphorylation of the enzyme was observed at physiological doses of 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35] Also, 1,25(OH) 2 D 3 binds and activates PI3K in human THP-1 myeloid leukemia cells, which is required for the induction of CD14 and CD11b but not of p21 CIP1 . 36 However, these studies did not explain how the particular activation of one or more signaling enzymes might modulate gene regulation by the ligand.…”
Section: Nuclear and Extranuclear Nr Effects Integratementioning
confidence: 99%